A study of factors affecting the labour productivity of construction projects in Sarawak - Ngu, Vivian, Xiang Wen; Sam, Man Keong (INTI International University, 2018)
The problems of affecting the Labour productivity of construction industry in Sarawak has been an issue of concern to most G7 contractors and professionals. This paper attempts to establish the significant factors that affecting the Labour productivity by conducting a survey method that relates to construction problems which encountered on sites. Sibu consists of twenty-five (25) problems while Kuching consists of seventy-nine (79) problems that could affect construction Labour productivity were identified and proposed a suitable framework to improve the Labour productivity of construction projects in future Sarawak. A qualitative survey was conducted using questionnaires. Twenty-five (25) questionnaires in Sibu were disturbed out of which 25 were returned (100%) while One hundred and ninety-six (196) questionnaires in Kuching were disturbed out of which 79 were returned (40%). The problems were ranked in their answers in term of ‘lowest effect’, ‘low effect’, ‘average effect’, ‘high effect’ and ‘highest effect’. The analysis of the survey was performed using the importance index, standard deviation, ranking, hypothesis test- one sample mean and two sample mean. This study can be seen as a more detailed study to be carrying by future research on the issue of Labour productivity affecting of construction projects among G7 contractors in Sarawak.